2010
DOI: 10.1007/s10637-010-9569-1
|View full text |Cite
|
Sign up to set email alerts
|

Restricted brain penetration of the tyrosine kinase inhibitor erlotinib due to the drug transporters P-gp and BCRP

Abstract: Both P-gp and Bcrp1 reduce the brain penetration of erlotinib. Although P-gp appears to be the most effective factor limiting the brain penetration of erlotinib, the highest brain accumulation was observed when Bcrp1 was also absent. Strategies to inhibit P-gp/BCRP in patients to improve delivery of (novel molecular-targeted) substrate agents, such as erlotinib, to the brain may be required for treatment of intracranial malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 39 publications
2
104
0
Order By: Relevance
“…According to the above results, lots of researchers put forward the subtle relationship between BBB permeability and tumor‐resistance protein that could remove toxins, drugs, or chemotherapies from the CNS. It would be a primary reason of failure to some extent 63. Besides, the EGFR T790M mutation could be another important mechanism for resistance to EGFR TKIs 64.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%
“…According to the above results, lots of researchers put forward the subtle relationship between BBB permeability and tumor‐resistance protein that could remove toxins, drugs, or chemotherapies from the CNS. It would be a primary reason of failure to some extent 63. Besides, the EGFR T790M mutation could be another important mechanism for resistance to EGFR TKIs 64.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%
“…In particular, the drug efflux transporters expressed at the BBB play a very important role in limiting the brain penetration of a wide variety of compounds including frequently used chemotherapeutics and novel targeted agents. Two well-established drug efflux transporters, ABCB1 (P-glycoprotein, P-gp, MDR1) and ABCG2 (Breast Cancer Resistance Protein, BCRP), are abundantly expressed in the human and murine BBB and restrict most newly developed kinase inhibitors such as erlotinib, lapatinib, and palbociclib (15)(16)(17). As a consequence, the usefulness of such agents in glioblastoma treatment might be attenuated by an inadequate brain penetration.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the inhibition of P-gp, also induced by verapamil. De Vries et al [45] also suggested the involvement of P-gp in the efflux of erlotinib. Giannoudis et al [42] and Gromicho et al [43] suggested that P-gp is also involved in dasatinib dependent efflux.…”
Section: Discussionmentioning
confidence: 98%